BASIC CONCEPTS OF THE GROUP APPROACH IN GUIDANCE AND COUNSELING - Habsy, Bakhrudin All; Febiyanti, Dela; Arsalan, Fidelalika Inasa Putri; Maulana, Hikmal; Arfianti, Yunica Putri (Jurnal Kajian Pendidikan dan Psikologi, 2024)
This study was conducted to ascertain the prevalence of individuals experiencing difficulties and requiring the assistance of counselors. In education, the counselor-to-student ratio is 1:150, meaning that one counselor is responsible for providing services to 150 pupils. Guidance and Counseling is an institution that provides assistance and support to individuals in order to help them achieve specific goals and address problems, while also ensuring their continued spiritual well-being. One of the services provided in the field of guidance and counseling is the utilization of a group setting as a method. The group approach in Counseling advice involves multiple counselors, as well as co-counselors who assist in the group counseling advice process. A study was undertaken to identify the techniques that can be utilized in the implementation of group counseling advice, employing the research methodology. Retrieve all pertinent citations related to subjects that pertain to techniques applicable in the process of counseling guidance within a group context. The study yielded several facilities that can enhance the group counseling guidance process, including: (1) understanding group methodologies There are two types of group approaches. The deployment of group guidance and counseling can be divided into three stages. This research aims to provide valuable insights for counselors to enhance their effectiveness in delivering counseling guidance services.